Modulating the release of drugs from alginate matrices with the addition of gelatin microbeads. (May 2014) - Qian, Qiang; Bonani, Walter; Maniglio, Devid; Chen, Jie; Migliaresi, Claudio
Injectable drug-loaded matrices and controlled release technology offer numerous advantages over conventional dosages. Cross-linkable alginate hydrogels have been proposed for in vivo injection, but their large initial burst release of encapsulated drugs represents a limitation for the transition to the clinical phase. To reduce this effect, a new drug delivery system was prepared by combining uncross-linked, drug-loaded gelatin microbeads with cross-linkable alginate solution. Gelatin microbeads ranging from 5 to 50 µm were obtained depending on gelatin concentration, stirring rate, and emulsifying time. The release behavior of drug-loaded gelatin microbeads encapsulated within cross-linked alginate gel was characterized both at room temperature and 37°C and compared with the release from gelatin microbeads and cross-linked alginate gel alone. Gelatin microbeads reduced the initial burst release of fluorescein from cross-linked alginate matrix, with a corresponding decrease in the release efficiency. Burst release in the first 2 h was reduced from 30% to about 5%, while cumulative release at 37°C declined from about 95% to 50% after 7 days. This system represents a promising approach for the development of novel and versatile injectable drug delivery systems.